Epidemiological and clinical characteristics of burns in adults: a 6-year retrospective study in a major burn center in Suzhou, China - Zhang, Yong; Su, Jiandong; Liu, Yunfeng; Sun, Ran; Sun, Ruizhu (Frontiers in Public Health, 2024)
Background: Burns are a prevalent form of unintentional injury and a significant public health concern in developing countries. We aimed to investigate the epidemiological and clinical characteristics of adult burn patients at a major center in Eastern China.This six-year retrospective study analyzed patients with varying degrees of burns between January 2017 and December 2022 at the Suzhou Burns and TraumaCenter. The study extracted demographic, clinical, and epidemiological data from electronic medical records for analysis.The study included 3258 adult patients, of which 64.3% were male. The largest age group affected 30-59-year-old adults (63.04%). Scalds were the leading cause of burns (1346, 41.31%), followed by flames (1271, 39.01%). The majority of burn hospitalizations were those with moderate burns (1791, 54.97%). The morbidity rate was low at 0.68%, while mortality was strongly associated with age, etiology, and total body surface area. Patients with certain types of burns, such as explosions, hot crush injuries, and electric burns had more operations, longer lengths of hospital stay, and higher costs compared to those with scalds and flame injuries.Conclusions: Different prevention strategies should be formulated according to different etiologies, ages, and genders.